Evaluation of a simple risk score to predict preterm pre‐eclampsia using maternal characteristics: a prospective cohort study. (28th March 2019) - Sovio, U; Smith, GCS
Abstract : Objectives: (1) To derive a simple risk score for preterm pre‐eclampsia based on the model used in the ASPRE trial, and (2) to compare it (i) with the original ASPRE algorithm, (ii) with the NICE Guideline score, and (iii) with and without biochemical and ultrasonic predictors. Design: Prospective cohort study. Setting: Cambridge, UK. Population or Sample: 4184 nulliparous women from the Pregnancy Outcome Prediction study. Methods: Maternal history model coefficients from the ASPRE algorithm were translated into a risk score, preserving the relative weight of each coefficient. Main outcome measures: Preterm delivery with a diagnosis of pre‐eclampsia. Results: The area under the ROC curve (AUC) for preterm pre‐eclampsia was 0.846 (95% CI 0.787–0.906) for the risk score and 0.854 (95% CI 0.795–0.914) for the original ASPRE algorithm ( P = 0.14). In all, 9.1% of women had a risk score of ≥30 and their risk ratio for preterm pre‐eclampsia was 13.3 (95% CI 6.3–27.8), sensitivity 57.1% (37.5–74.8%), false‐positive rate (1‐specificity) 8.8% (8.0–9.7%), and LR + 6.5 (4.6–9.1). The score had higher specificity than the NICE Guideline criteria. First trimester levels of PAPP‐A and PlGF were not predictive when included in a model with the risk score. In contrast, mean arterial pressure at booking and 20‐week uterine artery Doppler were independently associated with preterm pre‐eclampsia and the latter modestly increased the AUC (by 0.02). Conclusions: A simple risk score derived from the ASPRE screening study predictive model provided clinically useful prediction of the risk of preterm pre‐eclampsia. Tweetable abstract: A simple risk score derived from the ASPRE screening study provided clinically useful prediction of the risk of preterm pre‐eclampsia. Tweetable abstract: A simple risk score derived from the ASPRE screening study provided clinically useful prediction of the risk of preterm pre‐eclampsia.